2010
DOI: 10.1007/s00436-010-1760-y
|View full text |Cite
|
Sign up to set email alerts
|

The Nf-actin gene is an important factor for food-cup formation and cytotoxicity of pathogenic Naegleria fowleri

Abstract: Naegleria fowleri destroys target cells by trogocytosis, a phagocytosis mechanism, and a process of piecemeal ingestion of target cells by food-cups. Phagocytosis is an actin-dependent process that involves polymerization of monomeric G-actin into filamentous F-actin. However, despite the numerous studies concerning phagocytosis, its role in the N. fowleri food-cup formation related with trogocytosis has been poorly reported. In this study, we cloned and characterized an Nf-actin gene to elucidate the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 23 publications
1
46
2
1
Order By: Relevance
“…The heterolobosean amoebae do not possess any cytoskeleton-underlain cytostomes. However, the amoeba of Naegleria fowleri forms socalled amoebastomes, sucker-like surface structures that aid in phagocytosis (Sohn et al, 2010). The amoeboid stage is unknown (and possibly completely lost) in genera Lyromonas, Pharyngomonas, Pleurostomum, Percolomonas, and Stephanopogon.…”
Section: Pseudovahlkampfia Emersoni Fumarolamoeba Ceborucoi Willaermentioning
confidence: 99%
“…The heterolobosean amoebae do not possess any cytoskeleton-underlain cytostomes. However, the amoeba of Naegleria fowleri forms socalled amoebastomes, sucker-like surface structures that aid in phagocytosis (Sohn et al, 2010). The amoeboid stage is unknown (and possibly completely lost) in genera Lyromonas, Pharyngomonas, Pleurostomum, Percolomonas, and Stephanopogon.…”
Section: Pseudovahlkampfia Emersoni Fumarolamoeba Ceborucoi Willaermentioning
confidence: 99%
“…We previously reported that the pathogenicity of N. fowleri is a complex process which involves contact-independent pathways as well as contact-dependent pathways (29). In the contact-dependent mechanisms, the Nfa1 protein and actin protein were characterized and identified in N. fowleri infections (11,30). In addition, excretory-secretory proteins (ESPs) released from N. fowleri have also been identified, and these may play an important role in its pathogenicity (31).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess transcriptional differences between N. fowleri trophozoites grown in the three different media, a quantitative real-time RT-PCR using primers against potential pathogenicity factors (Aldape et al, 1994;Herbst et al, 2002Herbst et al, , 2004Hu et al, 1991Hu et al, , 1992Jung et al, 2009;Lee et al, 2007;Sohn et al, 2010) was performed. The primers used for the PCR are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…After biochemical and functional characterization, naegleriapores have been found to be cytotoxic to human cells (Herbst et al, 2004(Herbst et al, , 2002. Another protein involved in N. fowleri-induced cell destruction is Nfactin, which is specifically located around phagocytic foodcups and therefore plays an important role in phagocytic activity (Sohn et al, 2010). Studies using mAbs against Nfactin ( Lee et al, 2007) and gene silencing by small interfering RNAs targeting the Nf-actin gene (Jung et al, 2009) also suggested that Nf-actin is involved in in vitro cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%